2014
DOI: 10.1063/1.4900978
|View full text |Cite
|
Sign up to set email alerts
|

Optofluidic microvalve-on-a-chip with a surface plasmon-enhanced fiber optic microheater

Abstract: We present an optofluidic microvalve utilizing an embedded, surface plasmonenhanced fiber optic microheater. The fiber optic microheater is formed by depositing a titanium thin film on the roughened end-face of a silica optical fiber that serves as a waveguide to deliver laser light to the titanium film. The nanoscale roughness at the titanium-silica interface enables strong light absorption enhancement in the titanium film through excitation of localized surface plasmons as well as facilitates bubble nucleati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The heat generated by a laser beam focused onto an absorbing medium can, for example, drive particle accumulation or concentration depletion via the thermophoretic effect, even enabling single nanoparticle manipulation. , Photothermally facilitated phase changes, such as critical demixing, provide another means by which to thermally impart forces on the microscale . Photothermal matter manipulation can be used as a stand-alone method, or it can be utilized in conjunction to optical force manipulation methods such as optical tweezers. The ability to optically create a phase change in the form of localized bubbles in water using continuous wave (CW) illumination is particularly interesting from an application point-of-view such as in the context of particle manipulation, light-addressable optical elements, , steam generation, and microfluidic flow control. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat generated by a laser beam focused onto an absorbing medium can, for example, drive particle accumulation or concentration depletion via the thermophoretic effect, even enabling single nanoparticle manipulation. , Photothermally facilitated phase changes, such as critical demixing, provide another means by which to thermally impart forces on the microscale . Photothermal matter manipulation can be used as a stand-alone method, or it can be utilized in conjunction to optical force manipulation methods such as optical tweezers. The ability to optically create a phase change in the form of localized bubbles in water using continuous wave (CW) illumination is particularly interesting from an application point-of-view such as in the context of particle manipulation, light-addressable optical elements, , steam generation, and microfluidic flow control. , …”
Section: Resultsmentioning
confidence: 99%
“…7−9 The ability to optically create a phase change in the form of localized bubbles in water using continuous wave (CW) illumination is particularly interesting from an application point-of-view such as in the context of particle manipulation, 10−13 light-addressable optical elements, 14,15 steam generation, 16 and microfluidic flow control. 17,18 Many of the recent studies on photothermally induced bubble formation in water have utilized optically excited plasmonic metal nanostructures as the means for heat generation, 19−22 thus harvesting on the extensive understanding of plasmonic light manipulation accumulated over the last decades. Although we lack a detailed nanoscopic understanding of all aspects of the complicated processes involved in plasmon-induced bubble formation, recent experiments have begun to shed light on critical components of bubble formation, growth, and dissipation dynamics relevant for applications.…”
mentioning
confidence: 99%
“…The nanostructures are incorporated onto standard single-mode optical fibers; the light launched into the optical fiber is absorbed at the output end by the nanostructures and heat is generated and dissipated in the vicinity of the tip. Similar OFMHs have been previously used to heat liquids up to their evaporation point [20,21]. An attractive feature of these microheaters is their ease of fabrication with the use of off the shelf elements.…”
Section: Fabrication Of Optical Fiber Microheatersmentioning
confidence: 99%
“…Low‐power CW lasers have been used to heat metal films to nucleate bubble formation, but optical power loss through the optical path and exposure of fluid samples and biological species to this laser light are drawbacks to this technique. Kim et al reported a microheater for bubble generation directly within a fluid microchannel using a titanium film coated upon the end of an optical fiber. Depositing the metal on the fiber tool removed the requirement of this metallization fabrication step onto the microchannel system itself, which has been the traditional method used.…”
Section: Optical Fiber Tools For Manipulation Within a Microchannelmentioning
confidence: 99%